"Development Of A Method For SorbtsionSpectroscopic Detection Of Rhenium (Iii) Ion" - Mirzakhmedov Rustamjon Mirkhamidovich; Mirusmanova Farangis Babur's daughter (Peerian Journals Publishing, 2023)
he levels and optimal conditions of immobilization of the bismutol – 2 Reagent to various types of sorbents have been determined. It has been developed to find the mechanism of immobilization of the bismutol-2 Reagent to the carrier and to determine the optimal conditions and metrological properties of their formation of a complex with the rhenium (III) ion. A sorbtsion – spectroscopic method with high sensitivity and selectivity for the determination of the rhenium (III) ion has been shown. The developed sorbtsion – spectroscopic method was applied to Real objects (industrial waste technological water and cakes), the results were processed by the method of Mathematical Statistics and information about its application in the analysis
Keywords: Rhenium; ions; analytical